NF1 with Ewing’s Sarcoma and Thoracopulmonary PNET with Gastrointestinal Neoplasm: A Case Report of Synchronous Malignancies - Kovuri Umadevi; Syed Umar Ahmed; Gundluru Surendra Babu; Dola Sundeep (Journal of Clinical and Diagnostic Research)
Synchronous malignancies are rare and pose significant diagnostic and therapeutic challenges due to their complex presentations and diverse aetiologies. This report highlights two unique cases emphasising the importance of a multidisciplinary approach to management. The first case involves a 24-year-old male with Neurofibromatosis type 1 (NF1), presenting with Ewing’s sarcoma affecting the rib and lung. NF1, a genetic disorder caused by mutations in the NF1 gene, predisposes individuals to various malignancies, including sarcomas. This patient exhibited characteristic NF1 features such as café-au-lait spots, multiple neurofibromas, and Lisch nodules. Imaging revealed a destructive thoracic mass and histopathology, supported by immunohistochemistry, confirmed the diagnosis of Ewing’s sarcoma. The patient underwent surgical resection followed by chemotherapy, resulting in a favourable outcome. The second case describes a 75-year-old chronic smoker who presented with thoracopulmonary Primitive Neuroectodermal Tumour (PNET) and a high-grade dysplastic adenomatous polyp in the cecum. Imaging and histological evaluations confirmed the coexistence of these malignancies. The thoracic tumour was surgically resected and treated with a chemotherapy regimen, while the gastrointestinal lesion required a hemicolectomy. The patient’s postoperative course was uneventful, and follow-up assessments revealed no residual disease. These cases underscore the pivotal role of integrating advanced imaging, targeted biopsies, and molecular diagnostics to accurately identify and manage synchronous malignancies. Genetic predispositions, such as NF1, and environmental factors, including smoking, highlight the interplay of inherited and acquired risk factors in multifocal tumourigenesis. Multidisciplinary collaboration and individualised treatment strategies are critical for optimising patient outcomes, particularly in complex cases like these.